Long-term (20- to 25-year) results of an uncemented tapered titanium femoral component and factors affecting survivorship - Streit, Marcus R.; Innmann, Moritz Maximilian; Merle, Christian; Bruckner, Thomas; Aldinger, Peter; Gotterbarm, Tobias (Clinical orthopaedics and related research, 2013)
Background - Uncemented femoral components in primary total hip arthroplasty (THA) are commonly used today, but few studies have evaluated their survival into the third decade. - Questions/purposes - We evaluated (1) survivorship using femoral revision for any reason as the end point; (2) survivorship using femoral revision for aseptic loosening as the end point; and (3) patient-related and surgical risk factors for aseptic stem loosening at a minimum 20-year followup with an uncemented tapered titanium stem. - Methods - We reviewed the clinical and radiographic results of 354 THAs in 326 patients performed between January 1985 and December 1989 using an uncemented grit-blasted, tapered titanium femoral stem. Mean age at surgery was 57 years (range, 13-81 years). Kaplan-Meier survivorship analysis was used to estimate long-term survival. Minimum followup evaluation was 20 years (mean, 22 years; range, 20-25 years); at that time, 120 patients (127 hips) had died, and four patients (five hips) were lost to followup. Multivariate survival analysis using a Cox regression model was performed. - Results - Survivorship at 22 years with revision of the femoral component for any reason as the end point was 86% (95% confidence interval [CI], 81%-90%). Survivorship for femoral revision for aseptic loosening as the end point was 93% at 22 years (95% CI, 90%-96%). Undersized stems (canal fill index ≤ 80%) and stems in hips with cup revision were at higher risk for aseptic loosening (hazard ratio, 4.2 and 4.3, respectively). There was a high rate of acetabular revision in this series (38%), mostly related to smooth-threaded, cementless sockets. - Conclusions - Uncemented femoral fixation was reliable into the third decade. Age, male sex, and diagnosis were not associated with a higher risk of aseptic loosening. - Level of Evidence - Level IV, therapeutic study. See the Guidelines for Authors for a complete description of levels of evidence.
Published online: 14 May 2013
Gesehen am 11.03.2022